The Effect of Proposed Training Program for Enhancing and Developing the Arms Muscular Strength in the Free Swimming Amongst Physical Education Students at An-Najah National University - Ahmad "Mohammad Hassan" Mahmoud Aghbar (My University, 2016)
The aim of this study was to investigate the effect of proposed training program for enhancing and developing the arms muscular strength in the freestyle swimming amongst physical education students at An-Najah National University. To achieve that, the study was carried out on a purposive sample that consisted of (24) PE male students who registered in swimming course (2) (2015- 2016), and they were divided equally into an experimental group (n= 12) and a control group (n=12). Then, the proposed training program was applied for (8) weeks with (3) training units per week. Before and after the training program implementation, physical and skill tests were conducted including: (pull-up test (10s), 1-RM bench press (kg), freestyle swimming with arms frequency (repetitions), freestyle swimming with arms only (s), freestyle swimming with arms only (m/s), freestyle swimming (s), and freestyle swimming (m/s). After the data collection, SPSS software was used to analyze results. The results of the study revealed that the proposed training program has affected all the variables under study, with a significance level between pre and post tests in favor of post tests, and the percentages of change were as follows: pull-up test (10s) (35.61%), 1-RM bench press (kg) (11.58%), freestyle swimming with arms frequency (repetitions) (10.83%), freestyle swimming with arms only (s) (11.46%), freestyle swimming with arms only (m/s) (8.84%), freestyle swimming (s) (12.45%), and freestyle swimming (m/s) (14.87%). Therefore, the results of the study has shown that the traditional or regular training program has affected all the variables under study except pull-up test (10s), with a significance level between pre and post tests in favor of post tests, and the percentages of change were as follows: 1-RM bench press (kg) (4.68%), freestyle swimming with arms frequency (repetitions) (4.13%), freestyle swimming with arms only (s) (7.43%), freestyle swimming with arms only (m/s) (7.76%), freestyle swimming (s) (6.37%), and freestyle swimming (m/s) (7.07%). Finally, the results of the study indicated that there were statistically significant differences in the post test of all variables between the experimental and control groups in favor of the experimental group. The researcher recommends several recommendations where the most important is to give the arms muscular strength a great importance during the program training preparation to the sport season for its direct effect on developing the performance level of physical education students

هدفت الدراسة التعرف إلى أثر برنامج تدريبي مقترح لتنمية وتطوير القوة العضلية للذراعين في السباحة الحرة لدى طلاب تخصص التربية الرياضية في جامعة النجاح الوطنية، ولتحقيق ذلك أجريت الدراسة على عينة اختيرت بالطريقة العمدية من طلاب تخصص التربية الرياضية المسجلين بالفصل الدراسي الثاني في مساق سباحة (2) للعام الأكاديمي (2016/2015)، وبلغ عدد أفراد العينة (24) طالباً حيث تم توزيعهم إلى مجموعتين متكافئتين، المجموعة التجريبية وقوامها (12) طالباً والمجموعة الضابطة وقوامها (12) طالباً، و تم تطبيق البرنامج التدريبي المقترح لمدة (8) أسابيع وبواقع (3) وحدات تدريبية أسبوعيا، وقبل وبعد تطبيق البرنامج التدريبي تم إجراء الاختبارات البدنية و المهارية التالية على اليابسة: (اختبار الشد لأعلى على العقلة(10) ث لاحتساب عدد المرات التي تنفذ خلال الزمن المحدد، اختبار رفع اكبر ثقل لأعلى، مرة واحدة على (البنش) من الرقود على الظهر، واختبارات داخل الماء وهي اختبار تردد الذراعين سباحة حرة (25م) مره، اختبار حركات الذراعين من وضع الطفو الأفقي على البطن لمسافة (25م) بالثانية، اختبار المسافة المقطوعة لحركات الذراعين فقط (25م) لكل ثانية (بالمتر)، اختبار الزحف على البطن (سباحة حرة) بتوافق كامل لمسافة (25) م/ بالثانية، اختبار المسافة المقطوعة سباحة حرة توافق كامل (25م) لكل ثانية (بالمتر)، وبعد عملية جمع البيانات تم معالجتها إحصائياً باستخدام برنامج الرزم الإحصائية (SPSS) لتحليل النتائج. أظهرت نتائج الدراسة أن للبرنامج التدريبي المقترح تأثر على جميع المتغيرات قيد الدراسة لدى أفراد المجموعة التجريبية وبدلالة إحصائية بين القياسين القبلي والبعدي ولصالح القياس البعدي، وكانت النسبة المئوية للتغير على النحو الآتي: العقلة خلال (10) ث/ مره (35.61%)، رفع أكبر وزن على البنش/ كغم (11.58%)، سباحة حرة تردد ذراعين فقط/ مره (10.83%)، سباحة حرة باستخدام الذراعين فقط/ ث(11.46%)، سباحة حرة ذراعين فقط متر/ ث (8.84%)، سباحة حرة توافق كامل/ ث (12.45%)، توافق كامل متر /ث (14.87%). كما أظهرت نتائج الدراسة أن البرنامج الاعتيادي (التقليدي) أثر على جميع المتغيرات قيد الدراسة ما عدا متغير العقلة خلال (10) ث لدى أفراد المجموعة الضابطة وبدلالة إحصائية بين القياسين القبلي والبعدي ولصالح القياس البعدي وكانت النسبة المئوية للتغير على النحو التالي: العقلة خلال (10) ث/ مره (10.78%)، رفع أكبر وزن على البنش/ كغم (4.68%)، سباحة حرة تردد ذراعين فقط/ مره (4.13%)، سباحة حرة باستخدام الذراعين فقط/ ث (7.43%)، سباحة حرة ذراعين فقط متر/ ث (7.76%)، سباحة حرة توافق كامل/ ث (6.37%)، توافق كامل متر/ ث (7.07%)، كما أظهرت نتائج الدراسة وجود فروق ذات دلالة إحصائية في جميع متغيرات الدراسة بين أفراد المجموعة التجريبية والمجموعة الضابطة ولصالح أفراد المجموعة التجريبية، حيث يوصي الباحث بعدة توصيات أهمها إعطاء القوة العضلية في الذراعين أهمية كبيرة أثناء وضع البرنامج التدريبي بجميع مراحل الموسم الرياضي لتأثيرها المباشر في رفع مستوى الانجاز وتحقيق الأرقام القياسية، وكذلك عند وضع البرامج التدريبية الخاصة بطلاب تخصص التربية الرياضية في الجامعات وللاعبي منتخبات السباحة.
أثر برنامج تدريبي مقترح لتنمية وتطوير القوة العضلية للذراعين في السباحة الحرة لدى طلاب تخصص التربية الرياضية في جامعة النجاح الوطنية